A bacterial chloroform reductive dehalogenase: purification and biochemical characterization. Issue 6 (20th June 2017) - Jugder, Bat‐Erdene; Bohl, Susanne; Lebhar, Helene; Healey, Robert D.; Manefield, Mike; Marquis, Christopher P.; Lee, Matthew
Summary: We report herein the purification of a chloroform (CF)‐reducing enzyme, TmrA, from the membrane fraction of a strict anaerobe Dehalobacter sp. strain UNSWDHB to apparent homogeneity with an approximate 23‐fold increase in relative purity compared to crude lysate. The membrane fraction obtained by ultracentrifugation was solubilized in Triton X‐100 in the presence of glycerol, followed by purification by anion exchange chromatography. The molecular mass of the purified TmrA was determined to be 44.5 kDa by SDS‐PAGE and MALDI‐TOF/TOF. The purified dehalogenase reductively dechlorinated CF to dichloromethane in vitro with reduced methyl viologen as the electron donor at a specific activity of (1.27 ± 0.04) × 10 3 units mg protein −1 . The optimum temperature and pH for the activity were 45°C and 7.2, respectively. The UV‐visible spectrometric analysis indicated the presence of a corrinoid and two [4Fe‐4S] clusters, predicted from the amino acid sequence. This is the first report of the production, purification and biochemical characterization of a CF reductive dehalogenase. Abstract : The paper describes the purification and characterisation of a novel reductive dehalogenase, capable of dechlorinating trichloromethane to dichloromethane.